モノマー分子構造に基づく高分子安定化ブルー相の電気光学特性と熱力学的安定性の最適化 - 樋口, 博紀; 奥村, 泰志; 真井, 大輔; 小林, 武史; 菊池, 裕嗣; 町田, 銀平; 加畑, 雅之; 松本, 純一 (Proceedings of Japanese Liquid Crystal Society Annual meeting, 2016)
A cholesteric blue phase in the polymer-stabilized blue phase (PSBP) is thermodynamically stabilized by a polymer network (PN) which is formed by in-situ photopolymerization with monofunctional and bifunctional monomers. The PSBP is expected to be applied to next-generation liquid crystal displays because of its optical isotropy and fast response. The electro-optical properties and stabilities of PSBP are known to depend strongly on the structure of PN. In this study, we investigated the effect of monomer chemical structure on the properties of PSBP. In the case of using bifunctional monomer with alkyl spacer in the mesogenic core unit, the stability of PSBP was sufficiently improved and the operating voltage was successfully reduced due to a decrease of anchoring between PN and liquid crystal molecule.